Interlayer Expansion And Morphological Transformation Of Zinc-Aluminium Anionic Clay Through Methyl Orange Intercalation - Nursyafiqah Jori Roslan; Alsya Haneeza Mohd Shah; Nur Nadia Dzulkifli; Tengku Shafazila Tengku Saharuddin; Ruhaida Rusmin; Ainil Hawa Jasni; Hari Shankar Biswas; Vadym Kovalenko; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali (Institut Kimia Malaysia, 2026)
Indexed by SCOPUS / MYCITE